Evaluation of new yellow maize (Zea mays) inbred lines using line × tester analysis - Ismail, Mohammad Reda; El-Mouslhy, Tamer Talat (The Indian Journal of Agricultural Sciences, 2020)
This study evaluated 20 elite yellow maize (Zea mays L.) inbred lines which were crossed as female parents with three different testers as male parents, i.e. Gem. Pop. (Broad genetic base), Single cross 101 and Inbred line 100 represent (Narrow genetic base) at the Experiment Research Station of Moshtohor, Benha University, Egypt during 2014 summer. The resulting 60 top crosses with three commercial check hybrids i.e. SC.155, SC. Pioneer 3080 and TWC.352 were evaluated in a yield trail in two sowing dates during 2015 growing summer season. A randomized complete block design (RCBD) with three replications was used. The data were recorded on days to anthesis (AD), maturity date (MD), leaf area of upper ear (LA), ear length (EL) and grain yield per feddan (GYPF). The results showed that, sowing dates, crosses, lines, testers except for (MD) and line × testers mean squares were significant for all traits. The parental inbred lines (L-4, L-5, L-10, L-12, L-13, L-14 and L-19) possessed high GCA effects for grain yield and (L-6, L-7, L-10 and L-11) possessed high GCA effects for earliness. These lines could be utilized as promising inbred lines in a hybridization programme to develop high yielding and early maturity maize hybrids. The seven crosses (T-1×L-7, T-1×L-13, T-1×L-17, T-2×L-4, T-2×L-5, T-2×L-10 and T-2× L-12) which had out-yielded significantly the best check SC.3080 could be utilized for future breeding work as well as for direct release after confirming the stability of their performances observed in the current study.